Operational and Financial Performance of Andhra Pradesh State Financial Corporation (APSFC): An Overview - Viswanatha Reddy, C. (Indian Journal of Finance, 2013)
Andhra Pradesh State Financial Corporation [APSFC] is a term lending institution established in 1956 by merger of Andhra State Financial Corporation and Hyderabad State Financial Corporation for promoting small and medium-scale industries (SMEs) in Andhra Pradesh under the provisions of the State Financial Corporations Act, 1951. The APSFC as premier state level financial institution and as an integral part of the development financing system in the country has gained prominence for playing its role in the achievement of rapid and high quality industrial growth in Andhra Pradesh. It offers a package of assistance to the entrepreneurs to enable them to translate their project ideas into reality. The corporation has launched many entrepreneur-friendly schemes to provide term loans, working capital term loans, and special and seed capital assistance to suit the needs of various categories of entrepreneurs. The Corporation has completed five and half decades of dedicated service in industrial financing of tiny, small and medium-scale sector units and has been consistently contributing to the balanced regional development of the state. It has been continuously doing its best in every possible area of its operations to retain its premier position among the SFCs in the country. In order to provide an instant picture of the performance of the APSFC during the last ten years, the researcher undertook the present study. In this paper, the researcher has made an attempt to examine the no. of applications sanctioned with applied amount, flow of assistance in terms of sanctions and disbursements, flow of assistance to the small-scale sector, Recovery performance of the Corporation, Income and expenditure, Operating and net profit, Growth in net worth, Capital adequacy ratio, Asset quality and reduction of NPAs, Cost of borrowings and return on average assets. At the end of the analysis, some viable and useful suggestions are offered to tone up the overall performance of the Corporation for industrial development in Andhra Pradesh.